Information availability and return volatility in the bitcoin Market: Analyzing differences of user opinion and interest. Issue 3 (May 2019) - Yu, Ju Hyun; Kang, Juyoung; Park, Sangun
ABSTRACT: We study returns volatility and information availability in the rapidly growing Bitcoin market. The market microstructure for bitcoins is highly developed in terms of information generation and transfer. Therefore, returns volatility is highly likely to be affected by market information availability. We analyze the relationship between returns volatility and two independent variables, user opinion difference and user interest. This study adopted the GJR-GARCH model, appropriate for volatility studies. First, we find that, for volatility asymmetry, the Bitcoin market exhibits greater market efficiency than the general financial market. Also, the persistence of volatility is greater. The Bitcoin market is still relatively unregulated; hence, studying the relationship between information asymmetry and regulation in the market is salient. Moreover, we can infer that the ratio of reasonable users is high in the Bitcoin market. Second, the Bitcoin market supports the sequential information arrival hypothesis in that day trading volume, which is a proxy for user differences of opinion, has a statistically significant effect on returns volatility. Third, for the proxies of user interest, namely, the growth rate of page views on Google Trends and Wikipedia, only the growth rate of Google Trends shows statistically significant effects on Bitcoin returns volatility. This study can provide useful information to the financial market and policy makers on the behavior of the Bitcoin market, which may help to lower future entry barriers and opportunity costs of the Bitcoin market.